Fighting erasure and dispossession in the San Francisco Bay Area: putting archaeology to work for the Muwekma Ohlone Tribe - Panich, Lee M.; Arellano, Monica V.; Wilcox, Michael; Flores, Gustavo; Connell, Samuel (Frontiers in Environmental Archaeology, 2024)
The Muwekma Ohlone Tribe has long been involved in the archaeology and stewardship of their ancestral homelands, both through their own cultural resource management (CRM) firm and though collaborations with academic and CRM archaeologists. In this article, we build on the past 40 years of archaeological collaborations in the southern San Francisco Bay region and offer examples of how archaeologists can support tribal heritage and environmental stewardship by using the traditional purview of material culture in combination with a broader array of evidence and concerns. As presented in our brief case studies, the Muwekma Ohlone Tribe and scholars are working together to reclaim tribal heritage and promote Native stewardship in a cultural landscape that has been marred by more than 250 years of dispossession. We examine this work in the context of the renaming of ancestral sites, the public interpretation of Native heritage associated with Mission Santa Clara de Asís, archival research into the history of Indigenous resistance, as well as collaborative efforts to awaken traditional ecological knowledge in service of the Tribe's stewardship and land management goals.